Activation of GPR18 by cannabinoid compounds: a tale of biased agonism. (August 2014) - Console‐Bram, Linda; Brailoiu, Eugen; Brailoiu, Gabriela Cristina; Sharir, Haleli; Abood, Mary E
<x xml:space="preserve">Abstract</x> Background and Purpose GPR18 is a candidate cannabinoid receptor, but its classification as such is controversial. The rationale of the study presented herein was to consider the effects of N‐arachidonoyl glycine (NAGly) and cannabinoids via differential G‐protein coupled pathways, in addition to β‐arrestin signalling. Cellular localization of GPR18 receptors was also examined. Experimental Approach Calcium mobilization and ERK1/2 phosphorylation were quantified in a cell line stably expressing GPR18 (HEK293/GPR18 cells). In addition, using the DiscoveRx PathHunter® CHO‐K1 GPR18 β‐arrestin cell line, recruitment of β‐arrestin was quantified. Key Results Concentration‐dependent increases in intracellular calcium and ERK1/2 phosphorylation were observed in the presence of NAGly, abnormal cannabidiol (AbnCBD), O‐1602, O‐1918 and Δ9‐tetrahydrocannabinol (Δ9‐THC) in HEK293/GPR18 cells. The initial rise in intracellular calcium in the presence of NAGly, O1918 and THC was blocked by either Gαq or Gαi/o inhibition. The ERK1/2 phosphorylation was inhibited by Pertussis toxin and N‐arachidonoyl‐L‐serine (NARAS). Recruitment of β‐arrestin in the PathHunter CHO‐K1 GPR18 cell line revealed a differential pattern of GPR18 activation; of all the ligands tested, only Δ9‐THC produced a concentration‐dependent response. The localization of GPR18 receptors within the HEK293/GPR18 cells is both intracellular, and on the plasma membrane. Conclusions and Implications These findings suggest that GPR18 activation involves several signal transduction pathways indicative of biased agonism, thereby providing a plausible explanation for the apparent discrepancies in GPR18 activation found in the literature. Additionally, the results presented herein provide further evidence for GPR18 as a candidate cannabinoid receptor.